Recent development of planar microwave sensor for material characterization of solid, liquid, and powder: a review - Harry Sucitra Roslan; Maizatul Alice Meor Said; Zahriladha Zakaria; Mohamad Harris Misran (Institute of Advanced Engineering and Science, 2022)
Microwave is the most popular sensor in industrial applications for detecting material characterization. Over the past decade, microwave sensor is high demand, especially in medical for detecting cancer in the human body, agriculture for detecting moisture of soil, and freshness in the food industry. The previous study has shown that the high demands of the microwave sensor in industrial applications make researchers always think of new ideas to design microwave sensors to improves accuracy and sensitivity. This paper reviews an investigation of material characterization of recent developments of a planar sensor for various contaminants and parameter value of solid, liquid, and powder as material under test (MUT). Planar resonator sensor enhances the weakness of conventional sensors in bulky size, required a large volume of samples, and high cost. This planar sensor will differentiate MUT properties based on scattering parameters at various operating frequencies. The framework presented in this review paper includes new developments in resonator structure as well as advanced design of potential future research work. Previous studies will be objectively analysed and compared in order to gain a better understanding of microwave resonant sensors and to develop innovative concepts to further enhance application research involving material characterization.